(untitled) (Research, Society and Development, 2021)
The main objective of study was to reflect on the application of psychological tests in use in Brazil with the possibilities of validating them by the Brazilian Psychological Society, highlighting regarding the situations that show disorders related to school learning difficulties in children with normal intelligence, through a comprehensive assessment integrating intellectual functioning and personality organization. The psychoanalytical theoretical foundation holds that pathological psychic processes can decrease the function of curiosity and cause symptoms of intellectual inhibition or lack of concentration. The use of psychological assessment instruments is a necessary practice for the psychologist. In this perspective, this study aimed to investigate the use of psychologist. In this perspective, this study aimed to investigate the use of psychological assessment instruments by psychologists. Regarding the most used instruments, it was found that they are the personality assessment tests.